Expanding the library of divalent fucosidase inhibitors with polyamino and triazole-benzyl bridged bispyrrolidines. Issue 12 (24th February 2016) - Hottin, Audrey; Carrión-Jiménez, Sebastián; Moreno-Clavijo, Elena; Moreno-Vargas, Antonio J.; Carmona, Ana T.; Robina, Inmaculada; Behr, Jean-Bernard
Abstract : A small library of divalent fucosidase inhibitors containing pyrrolidine motifs were prepared and evaluated as α-fucosidase inhibitors. Abstract : A small library of divalent fucosidase inhibitors containing pyrrolidine motifs and separated by polyamino and triazole-benzylated spacers was prepared and evaluated as α-fucosidase inhibitors. Although a weak multivalent effect was observed in polyamino derived dimers, useful structural information can be deduced about the length of the bridge, the number of nitrogen atoms present and the moieties close to the pyrrolidine. Within these investigations one of the best α-fucosidase inhibitors containing a pyrrolidine framework was obtained (18, K i = 3.7 nM).